The Uprooting of Luis Cernuda and Agustí Bartra: A Comparative Vision from the Iberian Studies Viewpoint (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
This article aims to establish relations between two great poets in the 20th century: the Andalusian Luis Cernuda and the Catalan Agustí Bartra, from the point of view of Iberian Studies. The common parameters will be defined through the concept of uprooting and through María Zambrano’s metaphysics of exile. In this manner, we will analyze their works and biographies.Key words: Luis Cernuda, Agustí Bartra, Exile, María Zambrano, Iberian Studies.